2003
DOI: 10.1002/bem.10127
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency fields and teratogenesis

Abstract: Experimental studies that sought teratologic effects or developmental abnormalities from exposure to radiofrequency electromagnetic fields (RFEMF) in the range 3 kHz-300 GHz are critically reviewed for their possible consequences on human health. Those studies were conducted on beetles, birds, rodents, and nonhuman primates. Collectively, those experimental studies indicate that teratologic effects can occur only from exposure levels that cause biologically detrimental increases in body temperature. No reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 56 publications
1
27
0
1
Order By: Relevance
“…A major review of RF-induced teratology (which was developed as part of the process of developing IEEE C95. concluded that a temperature threshold of 41.5 C exists for thermally induced birth defects in animals [32]. This conclusion was based on animal studies that observed no foetal abnormalities in the animals studied (mostly rodents) below this temperature.…”
Section: Thermally Induced Teratogenesismentioning
confidence: 95%
“…A major review of RF-induced teratology (which was developed as part of the process of developing IEEE C95. concluded that a temperature threshold of 41.5 C exists for thermally induced birth defects in animals [32]. This conclusion was based on animal studies that observed no foetal abnormalities in the animals studied (mostly rodents) below this temperature.…”
Section: Thermally Induced Teratogenesismentioning
confidence: 95%
“…31 Numerous studies have evaluated developmental effects of RF fields on mammals, birds, and other nonmammalian species. 53,54 These studies have shown clearly that RF fields are teratogenic at exposure levels that are high enough to cause significant increases in temperature. There is no consistent evidence of effects at nonthermal exposure levels, although only a few studies have evaluated possible effects on postnatal development using sensitive end points such as behavioral effects.…”
Section: Health Risks To Children From Rf Fieldsmentioning
confidence: 99%
“…Galvin et al [1986] found that rats exposed prenatally (3 h/day for days 5-20 of gestation) to 2450 MHz microwaves (10 mW/cm 2 , SAR 2-4 W/kg) weighed more than sham exposed animals at 30 days of age. Additional material concerning thermal effects on the embryo and fetus is provided in a separate white paper [Heynick and Merritt, 2003]. …”
Section: Effects Of Rf Exposure On Early Developmentmentioning
confidence: 99%